The epidemiology, etiology, and future prophylactic options for cancers in Mainland China - Chen, Hongsen; Xu, Jie; Liu, Wenbin; Chen, Xi; Li, Ping; Cao, Guangwen (Frontiers in Oncology, 2025)
Mainland China accounts for 18.66% of the world’s population, 24.17% of global cancer new cases, and 26.44% cancer-related death worldwide in 2022. We aim to characterize the spatiotemporal distribution patterns of cancer burden, elucidate the main causes of high cancer burden, and propose evidence-based strategies for the prevention and control of major cancer types in Mainland China. We conducted a systematic search for relevant articles in PubMed and CNKI. We also analyzed the related data from two key databases: the 2022 dataset of the International Agency for Research on Cancer (IARC) and the records of China’s National Mortality Surveillance System (from 2004 - 2018). Lung cancer, primary liver cancer (PLC), gastric cancer, colorectal cancer (CRC), and esophageal cancer accounted for 67.50% of all cancer-related deaths. Age-standardized incidence rates (ASIR) and mortality rates (ASMR) of PLC, gastric cancer, and esophageal cancer showed downward trends, while their crude rates kept increasing. The ASMR of lung cancer kept decreasing in urban but increasing in rural populations. The burden of CRC kept increasing. Increase in cancer incidence could be attributed to the co-existence of the poverty-related risk factors like chronic infections and affluence-related ones like metabolic disorders. Primary prevention targeting to these modifiable risk factors is cost-effective. Aerobic exercise could decrease cancer occurrence and cancer-related death via decreasing systemic low-grade inflammation. The second and tertiary prophylactic options should be epidemiologically optimized. Targeting the major risk factors co-existed during economic transformation should be a cost-effective strategy to decrease cancer burden in transforming countries.